Greenhouse gas emission reduction and cost from the United States biofuels mandate. (March 2020) - Johansson, R.; Meyer, S.; Whistance, J.; Thompson, W.; Debnath, D.
Abstract: The United States biofuel mandate might be the largest operating program to reduce greenhouse gas (GHG) emissions. This paper uses regulatory information about abatement and compliance cost estimates to measure the greenhouse gas abatement cost curve of the mandate. Historical compliance costs per unit of biofuel appear readily available, yet findings here show that using these data along with observed biofuel quantities biases biofuel mandate abatement cost estimates upward. Unbiased estimation requires that related biofuel mandate costs and emissions are estimated along with associated market effects, including on fuel use, using an economic model. Moreover, this approach relates greenhouse gas abatement to the implications for crop prices and land use, taking account of interactions within the crop sector. Results show that the United States biofuel mandate causes up to 20 million metric tons of carbon dioxide equivalent abatement for compliance costs that are equivalent to carbon prices ranging up to $20 per ton, with a large part coming from reductions in petroleum product use as the mandate encourages substitution to biofuels. Abatement costs are reduced if ethanol is made at new facilities with fewer emissions or if petroleum output expansion causes greater emissions than the historical average. Findings also indicate that GHG abatement via the mandate is initially costly due to the nature of biofuel demand, there can be a trade-off between corn price increase and GHG reduction, and the increase in total area planted to crops in the U.S. is less important than the reallocation of land among crops. Graphical abstract: Image 1 Highlights: Biofuel mandate compliance costs can be used to estimate GHG abatement costs. Historical mandate compliance data, alone, can miscount costs and abatement. Economic simulations estimate the U.S. biofuel mandate abatement cost curve. Mandate GHG abatement costs relate to commodity prices and land use. Ethanol from new facilities and petroleum from new sources reduce abatement costs.